Propelling Morocco to new markets - Interview: Susanna Pak, staff writer, International Trade Centre - Susanna Pak (International Trade Forum, 2016)
From aerospace to seafood, Maroc Export helps small and medium-sized enterprises in a wide range of sectors to tap new export markets.